Multikriterijumski odabir optimalnog energetskog miksa u toku svetske energetske krize - Tomic, Aleksandra (Industrija, 2022)
Energy transition is the path for the transition to the sustainable energy. The key elements of such a transition are: the implementation of energy efficiency measures, It is known that the EU has established a clear legally binding framework for achieving the goals of the Paris Agreement from 2015, as well as ambitious goals through the 2030 Agenda. Serbia is also a signatory to the Sofia Declaration on the Green Agenda for the Western Balkans from November 10, 2020, which also obliges us to draft an Integrated Energy and Climate Plan. After the world health pandemic crisis, 2020, which was the year of stopping the economy, comes 2021, which is the year of recovery and accelerated economic growth, both in the world and in Serbia. The energy crisis, which occurs in the fall of 2021 with a radical jump in the prices of electricity and gas, which is a consequence of the change in economic relations in the world, the regrouping of capital and investments in energy.  The state will define the optimal energy mix in Serbia with the new Strategy, which will be based on existing energy sources, and a technical study of the optimal energy mix will also be done. All this will take into account the electricity system and energy security, as well as the economic and financial analysis of the proposed technical solutions of the optimal mix.. A multi-criteria analysis has been developed for the purpose of evaluating the results and selecting the scenarios on the basis of which the draft of the Integrated National Energy and Climate Plan will be prepared. The basis for this analysis should be the selection of the optimal energy mix that will be continuously monitored with special reference to the period of energy crises, and these are the periods when there are major disruptions in prices and availability on the world energy market. For Serbia, the Green Agenda is the path to climate-neutral Serbia, economic development and growth, the path to new and healthy jobs. The energy transition is not a race, but above all a marathon that should create.